Affecting Student Satisfaction with AI Tools in Higher Education: A Structural Equation Modeling Approach - Dahniar; Linggi, Cantika Randa; Sofyan, Vina Annisa; M. Miftach Fakhri; Pramudya Asoka Syukur (Jurnal MediaTIK, 2025)
Artificial Intelligence (AI) has increasingly become a central concern in the digital era, particularly within the context of higher education. This study aims to analyze the influence of AI tool usage on student satisfaction in the learning process. The research design employed is cross-sectional, with a sample of students from various departments at Universitas Negeri Makassar. Data were collected using a Likert-scale-based questionnaire and analyzed descriptively. The findings reveal that although students’ awareness of the potential of AI tools is relatively high, their actual experience in using them remains limited. Students acknowledged the positive benefits of AI tools in enhancing learning quality and information accessibility, yet only a small proportion actively utilized them. These results highlight the necessity for increased education and institutional support to encourage the adoption of AI tools on campus, enabling students to be better prepared to integrate them into their studies. This research contributes to the creation of a more adaptive learning environment and supports the development of student competencies in the digital era.